Lentheric Morny strike, 1974 (1974)
1974 1960-2000 "Lentheric Morny strike, 1974" [EP0017], 1974 In April 1974, 290 women at the Lentheric Morny perfume factory in Tottenham, North London took strike action because they were getting £7-8 less than the lowest male rate. Their average take-home pay was £15. 70 male workers came out in support and they won an increase of £2.25.